2021
DOI: 10.1038/s42256-021-00305-2
|View full text |Cite
|
Sign up to set email alerts
|

Code-free deep learning for multi-modality medical image classification

Abstract: A number of large technology companies have created code-free cloud-based platforms that allow researchers and clinicians without coding experience to create deep learning algorithms. In this study, we comprehensively analyse the performance and featureset of six platforms, using four representative cross-sectional and en-face medical imaging datasets to create image classification models. The mean (s.d.) F1 scores across platforms for all model–dataset pairs were as follows: Amazon, 93.9 (5.4); Apple, 72.0 (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 124 publications
(80 citation statements)
references
References 47 publications
2
59
0
2
Order By: Relevance
“…ICDR is applied in the EYEPACS dataset [ 24 ], Asian Pacific Tele-Ophthalmology Society dataset [ 25 ], Indian Diabetic Retinopathy Image Dataset [ 26 ], Messidor 1 and 2 datasets [ 27 ] (Table 1 ).…”
Section: Main Textmentioning
confidence: 99%
“…ICDR is applied in the EYEPACS dataset [ 24 ], Asian Pacific Tele-Ophthalmology Society dataset [ 25 ], Indian Diabetic Retinopathy Image Dataset [ 26 ], Messidor 1 and 2 datasets [ 27 ] (Table 1 ).…”
Section: Main Textmentioning
confidence: 99%
“…In contrast, automated machine learning (AutoML) techniques seek to accomplish these steps without user input. Recent studies assessing the feasibility of AutoML in healthcare have found promising results in comparison to bespoke models [11][12][13][14]. This represents an opportunity to enable clinicians with no computational background to leverage the power of ML.…”
Section: Introductionmentioning
confidence: 99%
“…The recent emergence of automated machine learning (AutoML) has been a major step in the democratisation of AI. AutoML describes a set of tools and techniques for streamlining model development by automating the selection of optimal network architectures, pre-processing methods and hyperparameter optimization 9 . Using a simple graphical interface and without writing code, users can build highly-accurate machine learning (ML) models.…”
Section: Introductionmentioning
confidence: 99%
“…Such models have been shown to rival hand-designed (bespoke) models 7 . Multiple studies explored the use of AutoML for the classification of medical images such as fundus photography and optical coherence tomography 7 , 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%